Effect of Contemporaneous Exchange Rate Changes on Value of Multinational Nonfinancial Companies Listed at Nairobi Securities Exchange - Avutswa, Nebart Oguda; Oluoch, Oluoch; Olweny, Tobias (International Journal of Scientific Research and Management (IJSRM), 2018)
The study investigates the effect of contemporaneous exchange rate changes on value of multinational nonfinancial companies listed at Nairobi Securities Exchange for period 2001-2016. Unexpected exchange rate changes and lagged exchange rate movements were used as control variables. The study adopted a two staged methodology. The first stage involved the determination of the foreign exchange exposure. At this point the REER is determined as the weighted average of the seven major currencies used by Kenya. The unexpected foreign exchange changes were determined using the ARIMA and GARCH model. The second stage of analysis involves a panel model where different aspects of foreign exchange exposure are regressed on firm value. The results indicated that contemporaneous exchange rate changes have a negative significant influence on the value of nonfinancial companies listed at the Nairobi Securities Exchange. The results of the study were inconclusive on the effects of lagged changes in exchange rates on firm value. The findings of the study reveal that unexpected exchange rate changes have a significant negative influence on firm value.